IDENTIFIKASI KARAKTER MORFOLOGI DALAM PENYUSUNAN DESKRIPSI JERUK SIAM (Citrus nobilis) DI BEBERAPA DAERAH KABUPATEN KARO - Dedi M. A. L. Tobing; Eva Sartini Bayu; Luthfi A.M. Siregar (Jurnal Agroekoteknologi, 2013)
ABSTRACTIdentification of Morphological Characterisric of Citrus nobilis at Some Areas of Karo District,supervised by EVA SARTINI BAYU and LUTHFI A. M. SIREGAR. Karo district is one of thecentres of citrus production in north Sumatera that have verygood prospect and market potential in ourcountry and overseas, so we need to increase quantity, quality, and continuity. The objective of thisresearch is to identification of morphological characteristic of citrus at Karo district. This research welldone at December 2012 to February 2013 using purposive sampling method. Data obtained fom theinterviews irectly to farmers with some obsevationn on the parameters to be analyzed using thesoftware Minitab 16.The result of this research indicate that morphological characteristic of citrus at 3villages on 37 samples have different morphological characteristic. The higest genetic relationship atC9 and C14 in Kacinambun Village sample (99,89%) and the lowest genetic relationship at A1 and A2 inSuka Village sample (39,44%).Key word : citrus, identification, morphological.